Economic valuation of national of national conservation of marine turtles a contingent valuation survey of Iloilo City residents. - Nuñal, Jeah Carmela Reyes
This study aims to determine the value of marine turtle species ; to identify government programs concerned with the conservation of marine turtles and to determine ways by which marine turtles can be conserved